2018
DOI: 10.1007/s41324-018-0203-1
|View full text |Cite
|
Sign up to set email alerts
|

Local determinants of household gas and electricity consumption in Randstad region, Netherlands: application of geographically weighted regression

Abstract: The previous studies on household energy consumption (HEC) are based on an implicit assumption: the impact of geographic determinants on HEC is uniform across a given region, and such impacts could be unveiled regardless of geographic location of households in question. Consequently, these studies have searched for global determinants which explain HEC of all areas. This study aim at examining validity of this assumption in Randstad region by putting forward a question regarding households' gas and electricity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…By application of aspatial methods, most of the previous studies have effectively ignored spatial heterogeneity of the determinants of energy poverty. A variety of previous studies, meanwhile, have shown that the best understanding of a wide range of phenomenaamong them academic achievement (Figueroa, Lim, and Lee 2016), effects of ozone pollution (Lin and Lu 2009), vulnerability to terrorism (Eisman, Gebelein, and Breslin 2017), household energy consumption (Mashhoodi 2018;Mashhoodi and van Timmeren 2018) and social vulnerability in slums (Jankowska, Weeks, and Engstrom 2011) is achieved only when spatial heterogeneity of the effects is taken into consideration. The result of this study is beneficial for future studies on energy poverty; there is a central question to start with: what are the spatially homogeneous and heterogeneous determinants of energy poverty?…”
Section: Discussionmentioning
confidence: 99%
“…By application of aspatial methods, most of the previous studies have effectively ignored spatial heterogeneity of the determinants of energy poverty. A variety of previous studies, meanwhile, have shown that the best understanding of a wide range of phenomenaamong them academic achievement (Figueroa, Lim, and Lee 2016), effects of ozone pollution (Lin and Lu 2009), vulnerability to terrorism (Eisman, Gebelein, and Breslin 2017), household energy consumption (Mashhoodi 2018;Mashhoodi and van Timmeren 2018) and social vulnerability in slums (Jankowska, Weeks, and Engstrom 2011) is achieved only when spatial heterogeneity of the effects is taken into consideration. The result of this study is beneficial for future studies on energy poverty; there is a central question to start with: what are the spatially homogeneous and heterogeneous determinants of energy poverty?…”
Section: Discussionmentioning
confidence: 99%
“…Wind speed, as it affects the air infiltration and exfiltration of buildings, ambient temperature of dwellings, and felt temperature (Sanaieian, Tenpierik, van den Linden, Seraj, & Shemrani, 2014;Van Moeseke, Gratia, Reiter, & De Herde, 2005); 9. Land cover and vegetation index in the zones, as they significantly affect HEC (Letu et al, 2010;Mashhoodi & van Timmeren, 2018).…”
Section: Objective and Approach Of This Studymentioning
confidence: 99%
“…The incorporation of such a holistic approach is essential, as the Dutch Climate Accord policies aim to phase out gas use for both cooking and heating in all dwellings by 2050 (Ministry of Economic Affairs and Climate Policy, 2019). Supposedly, the spatial pattern of electricity consumption in the dwellings will drastically shift because of these aims (Mashhoodi and van Timmeren, 2018). Therefore, the use of EVs is not about EVs per se.…”
Section: Discussionmentioning
confidence: 99%